Proceedings of the 2015 4th International Conference on Sustainable Energy and Environmental Engineering 2016
DOI: 10.2991/icseee-15.2016.207
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Configuration Analysis in Art Gallery based on Space Syntax mmComparison of Washington national gallery and the Shanghai art gallery

Abstract: Abstract. The article provides detailed and accurate design basis for building plan, studies a new theory and technology for the designers by researching from the spatial essentials to mathematically logic of spatial configuration and by using the method of spatially quantitative description, such as convex space, all-line visibility map, etc. The west part of national art gallery in Washington DC and Shanghai art gallery are taken as examples for analyzing spatially variable visibility and describe local spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Generally, it is rare for "all lines" analysis to be applied to the spatial analysis of individual buildings, but some scholars are becoming more interested in it. Qi and Chen applied "all lines" analysis to compare the spatial layout and spatial configurations of the Washington National Gallery and the Shanghai Art Gallery and found that there was an insufficient spatial logic relationship between the two that was difficult to detect by human perception [34]. Braga and De Saboya adapted "all lines" analysis to examine the mutual influence of spatial distribution and thermal performance on tropical and contemporary Brazilian dwellings [35], etc.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, it is rare for "all lines" analysis to be applied to the spatial analysis of individual buildings, but some scholars are becoming more interested in it. Qi and Chen applied "all lines" analysis to compare the spatial layout and spatial configurations of the Washington National Gallery and the Shanghai Art Gallery and found that there was an insufficient spatial logic relationship between the two that was difficult to detect by human perception [34]. Braga and De Saboya adapted "all lines" analysis to examine the mutual influence of spatial distribution and thermal performance on tropical and contemporary Brazilian dwellings [35], etc.…”
Section: Methodsmentioning
confidence: 99%